Perbandingan Kekuatan Geser Dan LenturBalok Bambu Laminasi Dengan Kayu - Pratama, Rosyid Setiawan Nur; , Ir. Aliem Sujatmiko, M.T; , Ir. Suhendro Trinugroho,M.T (2015)
There are three main types of materials in building construction, namely: wood, steel, and concrete. Nowadays, most of building function uses wood as its material from preparation to finishing. However, wood has some disadvantages, namely: wood may be damaged both fungi and termites, wood is more expensive enough and also difficult to be obtained. Based on the explanation above, bamboo can be used as material replacement. Bamboo has to be laminated in order to be used as material replacement of wood. There are three kinds of bamboo that is used. They are Petung bamboo, Ori bamboo, and Wulung bamboo. The researcher uses teak and mahogany as their comparator and Epoxy glue as their adhesive. The processes of bamboo lamination making are as a follows: The first is bamboo has to be cut into rectangles in order to become veneer. The second is dry the bamboo used oven until it reaches 15% moisture content. The third is glued the veneers which had been dried use Epoxy glue on both of the sides. The composition of the lamination uses carvel form. The test includes flexural strength and shear strength test. The result shows that the averages of shear strength are 24,59 MPa for teak, 17,19 MPa for mahogany, 10,22 MPa for Petung bamboo lamination and 9,42 MPa for both of Ori bamboo lamination and Wulung bamboo lamination. Meanwhile, the averages of flexural strength are 55,68 MPa for teak, 31,88 Mpa for mahogany, 22,61 Mpa for Petung bamboo lamination, 34,13 Mpa for Ori bamboo lamination, and 15,98 Mpa for Wulung bamboo lamination.